2009
DOI: 10.1186/1742-6405-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antiretroviral therapy and development of drug resistance in HIV-1 infected patients in Mombasa, Kenya

Abstract: Access to antiretroviral therapy (ART) is increasing in resource-limited settings (RLS) and can successfully reduce HIV-related morbidity and mortality. However, virologic failure and development of viral drug resistance can result in reduced treatment options and disease progression. Additionally, transmission of resistant virus, and particularly multi-drug resistance, could become a public health concern. This study evaluated treatment success and development of ART drug resistance after short-term treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…Agreement was interpreted as weak (0.400 Ͼ Ն 0.200), moderate (0.600 Ͼ Ն 0.400), strong (0.800 Ͼ Ն 0.600), nearly perfect (1.00 Ͼ Ն 0.800), and perfect ( ϭ 1.000). Sample size was estimated using Buderer's formula (38) with the following assumptions: HIVDR prevalence of 9.3% based on a previous study in Kenya (39), anticipated sensitivity equivalent to that obtained with the ViroSeq system of 99.65 (35), and a two-sided test with an alpha value of 0.05 and a precision value of 0.05. A minimum sample size of 60 was then required in order to obtain a sensitivity equivalent to that of the ViroSeq system.…”
Section: Methodsmentioning
confidence: 99%
“…Agreement was interpreted as weak (0.400 Ͼ Ն 0.200), moderate (0.600 Ͼ Ն 0.400), strong (0.800 Ͼ Ն 0.600), nearly perfect (1.00 Ͼ Ն 0.800), and perfect ( ϭ 1.000). Sample size was estimated using Buderer's formula (38) with the following assumptions: HIVDR prevalence of 9.3% based on a previous study in Kenya (39), anticipated sensitivity equivalent to that obtained with the ViroSeq system of 99.65 (35), and a two-sided test with an alpha value of 0.05 and a precision value of 0.05. A minimum sample size of 60 was then required in order to obtain a sensitivity equivalent to that of the ViroSeq system.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the county benefited from a measles mop-up immunisation programme supplemented with vitamin A given to children aged between 9 and 59 months. This Campaign was conducted between 3 rd and 7 th November 2012 and covered approximately 92.0% of the target population [12]. Narok County: A part of the study participants were drawn from Narok County.…”
Section: Study Sitesmentioning
confidence: 99%
“…Despite the reported high measles immunisation coverage of 85% -90% that followed, in 2012, repeat outbreaks occurred that comprised 3,056 cases of which 767 were confirmed, an increase of 102 confirmed cases from 2011 outbreaks [9,10]. This prompted a massive immunisation programme that covered more than 99% of the target population (9 -59 months old children) [11][12][13]. Genetic characterisation of measles virus has revealed 24 genotypes distributed within 8 genotypic groups as; A, B1-3, C1-2, D1-11, E, F, G1-3, and H1-2 [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-sectional study to determine treatment failure and drug resistance mutations among adults receiving first-line (3TC_d4T/AZT_NVP/EFV) and second-line (3TC/AZT/LPV/r) in Nairobi, Kenya, concluded that the detected accumulated resistance strains due to emergence of HIV drug resistance will continue to be a big challenge [7]. Another study carried out to evaluate treatment success and development of ART drug resistance at the Coast Province General Hospital, Mombasa, Kenya, revealed a high rate of treatment success after short term ART in patients treated at a public provincial hospital detected minority complex drug resistance profiles that were predictive of resistance to currently used second-line NRTIs and NNRTIs regimens [1]. In this article we present detailed data on DRMS from patients who had not started ARV and those who were failing with their implications on therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Development of HIV drug resistance is inevitable in patients on ART. Increase in antiretroviral therapy (ART) in resource-limited settings (RLS) will successfully reduce HIV-related morbidity and mortality [1]. The increase in ART coverage is expected to lead to an increase in drug-resistant strains among experienced patients.…”
mentioning
confidence: 99%